Assessment of a Single-Purpose Substance Abuse Facility for Committed Juvenile Offenders in Virginia, 1995-1997 - Gordon, Jill A. ([Verlag nicht ermittelbar], 2000)
The objective of this data collection was to provide a preliminary assessment of the effectiveness of treatment offered at the Barrett Juvenile Correctional Center, a substance abuse treatment facility in Virginia for convicted male offenders that began operation in late 1993. The center uses a holistic approach in the treatment of youth to identify the triggers for substance abuse and to investigate the relationship between substance abuse and delinquent behavior. For the facility assessment, various types of data from the Virginia Department of Juvenile Justice were gathered. Baseline data on each juvenile were obtained from the department's Reception and Diagnostic Center and consisted of demographic information and I.Q. scores, criminal history, and substance abuse history. Demographic variables include the youth's race, last grade placement, and with whom the youth lived. Youths' scores on standardized tests were also compiled, including SASSI, verbal I.Q., performance I.Q., and full-scale I.Q. scores. Criminal histories covered whether the committing offense was a felony or misdemeanor, the type of committing offense, the total number of committing offenses, whether a prior offense was a felony or a misdemeanor, the type of prior offense, the total number of prior offenses, the age at first criminal adjudication, age at commitment, and degree of delinquency. Alcohol and drug use data focused on the age at which alcohol was first used, number of times alcohol was used in the past year, age at which marijuana was first used, number of times marijuana was used in the past month, and whether the youth ever used cocaine, crack, inhalants, speed, depressants, hallucinogens, or other drugs. Another source of information was the youths' parole officers, who provided data on youths' criminal offending status and substance abuse at three, six, and twelve months after release from the center. Data obtained from parole officers assessing youths' improvement after leaving the center include whether they were rearrested, the type of offense if rearrested, the total number of offenses rearrested for, disposition, most serious offense overall, and youths' overall drug use.